Experimental characterization and modelling of textile reinforced masonry structures with the Equivalent frame method - Rizzo, Stefania (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung, 2022)
An innovative strengthening technique for the seismic retrofitting of masonry buildings is the fabric-reinforced cementitious matrix (FRCM). The system presented in this work is EQ-GRID, which consists of a multi-axial hybrid grid made of alkali-resistant glass and polypropylene fibres and a natural hydraulic lime mortar (NHL) as matrix. The results of the performed experimental campaign and the numerical modelling with the Equivalent frame method are presented and discussed in this work.